Do Demand Curves for Currencies Slope Down? Evidence from the MSCI Global Index Change - Hau, Harald; Massa, Massimo; Peress, Joel (Review of Financial Studies, 2010)
Traditional portfolio balance theory derives a downward sloping currency demand function from limited international asset substitutability. Historically, this theory enjoyed little empirical support. We provide direct evidence by examining the exchange rate effect of a major redefinition of the MSCI Global Equity Index in 2001 and 2002. The index redefinition implied large changes in the representation of different countries in the MSCI Global Equity Index and therefore produced strong exogenous equity flows by index funds. Our event study reveals that countries with a relatively increasing equity representation experienced a relative currency appreciation upon announcement of the index change. Moreover, stock markets that are upweighted (downweighted) feature a higher (lower) permanent comovement of their currency with the basket of other MSCI currencies.